Expanding DP4: application to drug compounds and automation. Issue 16 (5th April 2016) - Ermanis, Kristaps; Parkes, Kevin E. B.; Agback, Tatiana; Goodman, Jonathan M.
Abstract : The DP4 parameter, which provides a confidence level for NMR assignment, has been widely used to help assign the structures of many stereochemically-rich molecules. Abstract : The DP4 parameter, which provides a confidence level for NMR assignment, has been widely used to help assign the structures of many stereochemically-rich molecules. We present an improved version of the procedure, which can be downloaded as Python script instead of running within a web-browser, and which analyses output from open-source molecular modelling programs (TINKER and NWChem) in addition to being able to use output from commercial packages (Schrodinger's Macromodel and Jaguar; Gaussian). The new open-source workflow incorporates a method for the automatic generation of diastereomers using InChI strings and has been tested on a range of new structures. This improved workflow permits the rapid and convenient computational elucidation of structure and relative stereochemistry.